Fracture humerus during caesarean section: a case report - Kumar, Rakesh; Mundhra, Rajlaxmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Caesarean section is considered safer than vaginal delivery in risks involved for birth injury. Birth injury is more common in vaginal breech deliveries but are also encountered in caesarean section. Authors hereby report a case of long bone fracture in a neonate which occurred during caesarean section. The neonate presented with erb’s palsy and wrist drop. Baby was admitted and was managed with a U slab (pop slab) with physiotherapy which was later replaced by arm body strapping. Obstetricians and Paediatricians should remain vigilant for the rare chance occurrence of birth injuries during caesarean section also so that cases are not missed and managed timely for prevention of disability and deformities later.